Copgraph beetles in the conservation of the dry forest of the Enrique Quintero Arenas Botanical Garden, UFPS-Ocaña - Wendy Rocío Soto-Castro; José Julián Cadena-Morales (AiBi Revista de Investigación, Administración e Ingeniería, 2021)
The coprophages are a group of individuals of great importance in the ecological dynamism of natural areas given their specific adaptability of the species and their relationship to their distribution since it influences the quality and quantity of the resources they need for their development. In this sense, a study of mangrove coprophages in the dry inter-Andean forest on the grounds of the Universidad Francisco de Paula Santander Ocaña, as a fundamental basis for the in situ conservation of natural areas. For the taxa collection, it was carried out by random sampling within the area, using Pitfall traps made with 16-ounce vessels; inside they contained alcohol and soapy water for the capture and preservation of the species, where the attractant used was decomposing meat and pig manure. The traps were arranged in four sites (M1, M2, M3, and M4), with 15 traps in each of them. In total 824 individuals were registered, distributed in thirteen species, where the abundant corresponds to Canthidium aurifex, Eurysternus scarabaeus and Canthidium sp with 799 (96.96%) toral individuals; while 3.4% (25) of the species with six and one individual correspond to Oryctes nasicornis, Odontotaenius disjunctus, Monochamus sp, Hololepta quadridentata, Calathus fuscipes, Neoathyreus exacavatus, Onthophagus striatulus, Dichotomous sp, Copris lunares, Eurysternus marmoreusIn this way, the differences of two zones are documented, one with acidic to slightly acidic soils and another abundant in phosphates and little organic matter, given that the greater information of coprophages is influenced by environmental variables, in addition this abundance is related to abrupt edges adjacent to agricultural farms, where land tenure has changed the structure and functioning of the landscape typical of anthropic areas.